2015
DOI: 10.1016/j.fuel.2014.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of lift-off length and ignition delay of a two-component diesel surrogate

Abstract: Elsevier Payri, R.; Viera Sotillo, JP.; Pei, Y.; Som, S. (2015). Experimental and numerical study of liftoff length and ignition delay of a two-component diesel surrogate. AbstractUnderstanding and controlling mixing and combustion processes is fundamental for the ever more demanding pollutant regulations and fuel consumption standards of direct injection diesel engines. The fundamentals of these processes haven been long studied from both experimental and numerical perspectives. As numerical models become m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 42 publications
(68 reference statements)
4
54
0
Order By: Relevance
“…Experimental results by multiple authors [27,29,[31][32][33][34] have shown the e ect of oxygen concentration, ambient temperature, density and injection pressure on ignition delay. As theoretically explained by Petrucci et al [35], increasing oxygen concentration and ambient temperature accelerate oxidation reactions, resulting in a reduction in ignition delay.…”
Section: Impact Of Operating Conditions On Ignition Delaymentioning
confidence: 99%
“…Experimental results by multiple authors [27,29,[31][32][33][34] have shown the e ect of oxygen concentration, ambient temperature, density and injection pressure on ignition delay. As theoretically explained by Petrucci et al [35], increasing oxygen concentration and ambient temperature accelerate oxidation reactions, resulting in a reduction in ignition delay.…”
Section: Impact Of Operating Conditions On Ignition Delaymentioning
confidence: 99%
“…Specifically, the chemiluminescence of OH ⁄ is a technique widely used in combustion investigation [14,16,15], in which OH ⁄ radicals are emitted when they decay at their ground state and the generated luminescence can be captured to several diagnostics as the detection of high-temperature regions or estimations of the equivalence ratio [19]. In this connection, before going further in the technique explanation, it is pertinent to define the ignition parameter that was characterized in this work using OH ⁄ chemiluminescence method: the lift-off length.…”
Section: Oh ⁄ Chemiluminescencementioning
confidence: 99%
“…and inert sprays penetrations [12,13], determining generally the faster spray expansion in presence of combustion. This technique has been also employed for ignition delay measurements under the knowledge of the light intensity characteristics of each combustion phase [14,15]. Furthermore, several authors have underlined the effect of air-fuel mixture on soot formation, which can be associated with lift-off length [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…An additional explanation is found in the higher injection pressure directly after needle lift. Payri et al [71] have shown in their experiments and simulations that the FLOL increases slightly with injection pressure.…”
Section: Flame Lift Off Lengthmentioning
confidence: 97%